6AP wheel: A new transformable robotic wheel for traction force improvement and halting avoidance of a UGV on soft terrains. Issue 10 (3rd October 2022) - Mardani, Arman; Ebrahimi, Saeed; Alipour, Khalil
Abstract: This article develops a new reconfigurable wheel composed of Six Adaptive Prisms (6AP). Then, an Unmanned Ground Vehicle (UGV) is established with four proposed wheels to investigate some primary tasks. Wheel-soil formulation of the considered UGV is derived by Soil Contact Model (SCM). Considering SCM results, equations of motion of this robotic system are derived using the Lagrange approach. After that, 3D gap analysis and experimental geometric investigations are used to show the similarity between the outer form of the new mechanism and circumscribed circle. Furthermore, some advanced simulations such as getting unstuck from sand and reconfiguring of 6AP wheels are conducted to demonstrate the merits of the suggested wheel as compared with simple wheels.